The unavoidable depopulation problem of Japan. - Chong, Yuan Ping. (2010)
Our group is interested in finding out what are the reasons and effects for declining population trend in Japan. After completing a detailed research, our group has chosen to do analysis for our selected reasons and effects using data from various sources. Our group has also chosen to do a comprehensive survey on the Singapore residents to find out what encourages them to have more children. Using paired comparison method, the results indicate that all variables affect birth rates positively, but monetary rewards such as baby bonus and parenthood tax rebate affect people the least. Economic explanations for the results are provided in the report itself.